2011
DOI: 10.4236/sgre.2011.24037
|View full text |Cite
|
Sign up to set email alerts
|

Study and Implementation on Batteries Charging Method of Micro-Grid Photovoltaic Systems

Abstract: In the micro-grid photovoltaic systems, the random changes of solar radiation enable lead-acid batteries to experience low SOC (State of Charge) or overcharged for periods of time if directly charged with such traditional methods as decreased charging current, which will reduce lifetime of batteries. What’s more, it’s difficult to find a proper reduction coefficient in decreasing charging current. To adapt to the random changes of circumstance and avoid selecting the reduction coefficient, a new fast charging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…9 [15] [16]. It is observed that the maximum charging voltage or overcharging voltage set to V g is about 2.4 V/cell.…”
Section: Decreased Charging Current Based On Soc Methodsmentioning
confidence: 99%
“…9 [15] [16]. It is observed that the maximum charging voltage or overcharging voltage set to V g is about 2.4 V/cell.…”
Section: Decreased Charging Current Based On Soc Methodsmentioning
confidence: 99%
“…In this case, the charger needs to be rated only for the rating of the battery. In the configuration presented in [3,4], independent DC-DC converters are required to connect the battery and PV array to the DC link as shown in Figure 2c.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, charger needs to be rated only for the rating of the battery. In the configuration presented in [2] and [3], Independent DC-DC converters are required to connect battery and PV array to DC link as shown in Figure 2 An optimized operation of a Dual Active bridge (DAB) converter feeding a PV inverter connected to the grid is presented in [4] and [5]. Isolation between Grid and DC side is provided through high-frequency transformer used in DAB as shown in Figure 2(d).…”
Section: Mode3mentioning
confidence: 99%